Centralized DEA-based reallocation of emission permits under cap and trade regulation. (10th October 2019) - Momeni, Ehsan; Lotfi, Farhad Hosseinzadeh; Saen, Reza Farzipoor; Najafi, Esmaeil
Abstract: Cap-and-trade is regarded as the most effective approach to control and reduce greenhouse gas emission. How to perform the reallocation in a fair way is very critical to control total amount of emissions and improve trade mechanism. It has been proved that data envelopment analysis (DEA) is an effective way for reallocation. The objective of the present paper is to develop a centralized DEA model to reallocate emission permits in the cap and trade system based on countries efficiencies. Presented model considers all decision making units (DMUs) together and improves whole efficiency of them by reducing total emission permit as undesirable outputs. Also, this model determines amount of emitted gases that can be reduced without reducing other outputs. To demonstrate the applicability of model, a case study is presented. Sensitivity analysis is carried out to investigate the impact of the some parameters on the results.